Caution with the continued use of Jeffrey Beall’s “predatory” open access publishing lists - Teixeira da Silva, Jaime A. (AME Medical Journal, 2017)
Mr. Jeffrey Beall, a librarian at the Auraria Library, University of Colorado Denver, with an MA in English and Spanish, but no PhD, became famous because of his blog, www.scholarlyoa.com. Beall’s blog thus became synonymous with Beall, and Beall with his blog, and both are used interchangeably in this paper. Thus, praise or criticisms that one regularly reads in social media or blogs that refer to one, in general refer to both.